2013
DOI: 10.1371/journal.pone.0067093
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Long-Term Demography and Weather in a Sub-Arctic Population of Common Eider

Abstract: Effects of local weather on individuals and populations are key drivers of wildlife responses to climatic changes. However, studies often do not last long enough to identify weather conditions that influence demographic processes, or to capture rare but extreme weather events at appropriate scales. In Iceland, farmers collect nest down of wild common eider Somateria mollissima and many farmers count nests within colonies annually, which reflects annual variation in the number of breeding females. We collated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…This development was anticipated in our work 2005–20093. In recent years, large common eider population declines have been observed also in Iceland19. We suspect thiamine deficiency to be the cause of these recent population declines.…”
Section: Resultssupporting
confidence: 63%
“…This development was anticipated in our work 2005–20093. In recent years, large common eider population declines have been observed also in Iceland19. We suspect thiamine deficiency to be the cause of these recent population declines.…”
Section: Resultssupporting
confidence: 63%
“…Females that have abandoned breeding or for other reasons have not appeared at the breeding colony have been reported from colonies in Finland [44] and on Iceland [45] in years with poor food availability. Emigration to other colonies is another explanation for the reduced number of breeders, although this explanation seems unlikely because countrywide surveys of breeding eiders in Denmark have shown stable numbers after 1995 with no increase in colonies adjacent to Christiansø [41].…”
Section: Discussionmentioning
confidence: 99%
“…Spring migration took place from late March to late May. Other studies have shown that the breeding populations, especially in Norway (Fauchald et al 2015) but also in Iceland (Jónnsson et al 2013), are decreasing. The authors conclude that the winter survival of Svalbard breeding birds may be at a risk if these declines reflect deterioration of feeding habitat quality or other environmental conditions during winter.…”
Section: Partmentioning
confidence: 92%